CONCEPTUAL THREE PHASE KDD MODEL AND FINANCIAL RESEARCH - Bagga, Dr. Simmi (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2005)
KDD model becomes used in financial process. Data Mining tools can be used to improve the efficiency of the professionals. The integration of Data Mining tools with the traditional financial research methods is relatively a new concept. If Data Mining tools for Financial are developed then it make the process fast, cheaper and relatively much more efficient. In this paper we have discussed the three phase model of KDD on Financial Research.